Oral ulcers as a presentation of secondary syphilis. (23rd July 2018) - Thakrar, P.; Aclimandos, W.; Goldmeier, D.; Setterfield, J. F.
Summary: The incidence of syphilis is increasing, and it typically presents in patients with known risk factors, often to genitourinary physicians. Patients presenting to a dermatologist or ophthalmologist will more likely have secondary syphilis, with the potential for having the associated complications. Early recognition is therefore vital to limit both the disease and risk of further contact spread. In this review, we include two case histories demonstrating the value of recognizing oral signs. Additionally, we review the currently accepted diagnostic and therapeutic recommendations. Abstract : Clickhere for the corresponding questions to this CME article.